Проєктування серверної частини системи керування та моніторінгу зарядними станціями - Чубаров, Є. Е.; Рубель, Д. А. (ХНУРЕ, 2024)
This work is devoted to the design of the backend of the control and monitoring system for charging stations for electric vehicles. The use of the Open Charge Point Protocol (OCPP) protocol to ensure compatibility between different charging stations was considered. Also, application of microservice architecture to ensure modularity, scalability, and reliability with Docker and Kubernetes to ease deployment and increase system availability were considered.
Keywords: керування зарядними станціями; Open Charge Point Protocol (OCPP